Natural Resources Uses - Mohamad Suhaidi, Salleh; Neilson Ilan, Mersat; Kamsiah, Ali; Farah, Zaini; Regina Garai, Abdullah; Haslina, Hashim (UNIMAS Publisher, 2022)
Samunsam ids Sarawak's oldest Wildlife Sanctuary and one of several Important Birds Areas in the State. The site gazetted in 1979, and in line with state development plan, a number of areas near the Sanctuary have been identified as of economic importance. Therefore, the Samunsam area is likely to see significant impacts in the near future, derived from an isolated area to more accessible to human.